OPTIMASI STRUKTUR HELIDECK DENGAN VARIASI BEBAN HELIKOPTER - Anwar, Anwar; Bachmid, Reza (Politeknik Negeri Jakarta, 2020)
ABSTRACTHelideck is a helicopter landing field located on ships and offshore buildings. The helideck structure must have the strength to withstand the loads of the helicopter landing. The purpose of this study is to determine the maximum strength of the helideck structure. Helideck structure strength calculations used SACS structural strength software by performing a running analysis adopting the finite element method. The maximum calculation results value that the helideck structure can hold is the type of helicopter with a maximum weight of 155 kN with a working stress of 37,80 N/mm2 and an interaction value of (IR) 1. The helideck structure will encounter a yield stress or fracture with an IR value > 1.Keywords : Structure Strength, Helideck, Helicopter LoadABSTRAKHelideck merupakan lapangan pendaratan helikopter yang terdapat pada kapal dan bangunan lepas pantai, struktur helideck harus memiliki kekuatan yang mampu menahan beban pendaratan helikopter. Tujuan penelitian ini adalah untuk menghitung kekuatan maksimum dari struktur helideck, perhitungan kekuatan struktur helideck menggunakan software kekuatan struktur SACS dengan melakukan running analisis yg mengadopsi metode elemen hingga.hasil penelitian menunjukkan nilai maksimum yang dapat ditahan struktur helideck adalah tipe helikopter dengan berat maksimum 155 kN dengan tegangan kerja maksimum sebesar 37,80 N/mm2 dan nilai interaksi rasio (IR) 1. Struktur helideck akan mengalami tegangan leleh atau patah dengan nilai IR > 1.Kata kunci : Kekuatan Strutur, Helideck, beban helikopter